2022
DOI: 10.1038/s41528-022-00226-z
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive active-powering pressure sensor enabled by integration of double-rough surface hydrogel and flexible batteries

Abstract: A conductive, elastic, and biocompatible hybrid network hydrogel was prepared by cross-linking of locust bean gum, polyvinyl alcohol, and carbon nanotubes, yielding a rough top surface and smooth bottom surface. The merging of the two pieces of hydrogel flat face to flat face forms a highly elastic hydrogel with double-rough surfaces. A piezoresistive sensor assembled with the double-rough surface hydrogel sandwiched between two carbon cloth electrodes exhibits a high sensitivity (20.5 kPa-1, 0-1kPa), a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Figure and Table S1 show the sensing performance comparison between the fabricated flexible pressure sensor and other high-performance piezoresistive sensors reported in the literature. ,,, It is found that most pressure sensors cannot achieve high sensitivity and wide linear range simultaneously through material selection and structural design, exhibiting a trade-off between these two properties. In this work, the PI@Ag sensors possess both high sensitivity (197 kPa –1 ) in a medium-pressure region (10–20 kPa) as well as relatively high sensitivity (13.73 kPa –1 and 47.6 kPa –1 ) in the low- (100 Pa–10 kPa) and high-pressure regions (20–50 kPa).…”
Section: Resultsmentioning
confidence: 99%
“…Figure and Table S1 show the sensing performance comparison between the fabricated flexible pressure sensor and other high-performance piezoresistive sensors reported in the literature. ,,, It is found that most pressure sensors cannot achieve high sensitivity and wide linear range simultaneously through material selection and structural design, exhibiting a trade-off between these two properties. In this work, the PI@Ag sensors possess both high sensitivity (197 kPa –1 ) in a medium-pressure region (10–20 kPa) as well as relatively high sensitivity (13.73 kPa –1 and 47.6 kPa –1 ) in the low- (100 Pa–10 kPa) and high-pressure regions (20–50 kPa).…”
Section: Resultsmentioning
confidence: 99%
“…c) Sensitivity and detection range of our sensor with DR‐5 W hydrogels in comparison with other reported sensors based on hydrogels. [ 18,20,30–34 ] d) The changes in relative current of the sensor fabricated with DR‐5 W hydrogels pressed by different amounts of rice grain. The inset shows optical image of a rice grain during testing.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity and detection range of the proposed sensor were also compared with other sensors based on hydrogels. [18,20,[30][31][32][33][34] As illustrated in Figure 3c, the sensor obtained with DR-5 W hydrogels showed superior performance. Therefore, the sensor with DR-5 W hydrogels was selected for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations